A method of detecting sea fogs using CALIOP data and its application to improve MODIS-based sea fog detection. (March 2015) - Wu, Dong; Lu, Bo; Zhang, Tianche; Yan, Fengqi
Abstract: A method to detect sea fogs from the measurement data acquired by the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) aboard the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite is proposed in this paper. Because of the unique capability of vertical-resolved measurements, sea fogs and low clouds can be more easily distinguished in the CALIOP data compared with passive satellite measurements. Yellow Sea where sea fogs occur frequently is selected to test the method. Nine cases of daytime sea fog events from 2008 to 2011 in the Yellow Sea are studied intensively to characterize the remotely sensed radiation properties of various targets, such as clear-sky sea surface, sea fog, low cloud and high cloud. These fog cases are then used in an attempt to evaluate sea fogs identified from the MODIS measurements. The method proposed in this paper can also be used for nighttime cases. Multi-year sea fog dataset can be made from the CALIOP measurement and used to validate the MODIS sea fog detection. Highlights: A method of sea fog detection from the CALIOP measurements is proposed. CALIOP VFM and 532-nm attenuated backscatter products are integrated used. Sea fogs and low clouds can be more easily distinguished in the CALIOP data. 9 Cases of daytime sea fog events in the Yellow Sea are selected to test the method. The MODIS sea fog detections are evaluated using the collocated CALIOP data.